Sistem Informasi Pendaftaran Peserta Didik Baru Berbasis Web Pada Sekolah Menengah Pertama Sulthan Kabupaten Bogor - Syahla Salsabila Syahla; Muhammad Cordiaz (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
The activity of accepting new students is a routine activity carried out by the school every new school year. The system used at SMP Sulthan is currently in the process of registering new students by coming to school to see the registration schedule and filling out forms provided by the committee. This study aims to design a web-based New Student Registration System (PSB) at SMP Sulthan, to make it easier for prospective new students to register. In the development of this system using the waterfall strategy sequential method (regular waterfall strategy) the stages of development are system analysis (system analysis), system design (system design), program code writing (coding) and program testing (testing). The results of this study indicate that this system is able to manage the registration process of new students at SMP Sulthan using PHP and MYSQL. Keywords: New Student Admissions Information System Based on Web, HTML, Phpmyadmin